SURVEY PERILAKU MENDENGARKAN RADIO DI JAKARTA - Siti Dewi Sri Ratna Sari; Ervan Ismail (Universitas Mercu Buana, 2016)
This research is to find out the profile of radio broadcasting’s content in Jakarta and to look for measured data as the parameter to assess radio broadcasting programs and the radio listeners profile in DKI Jakarta. The research methodology is survey with 1000 respondents as the sample with 2.24% margin of error and 95% credibility level. The sampling method used is Multistage Random Sampling from 5 out of 6 DKI Jakarta Province areas, except Thousand Islands Regency. Data collection technique used is face to face personal interview by giving gift to the respondents. Research result describes the profile of radio listeners is middle class productive age working men and women whose prime reason listening to radio is music as their pastime. Respondents are categorized as medium listeners with 1.87 hour as their average of listening to radio. Nevertheless, the prime time is covering the whole day both while they are listening at home and while they are mobile. Research found that respondents are already satisfied by the radio programs in Jakarta. The competition of radio stations in Jakarta based on their listeners is Gen FM at the top with 44.6%, followed by Bens Radio, Elshinta, I-Radio, Prambors, CBB, and so on. An interesting finding is that radio’s function to deliver social communication is fulfilled by placing religious speech and information as the second and the third most preferable programs with 9.8% and 8.0% below music program. Penelitian ini bertujuan untuk mengetahui profil isi siaran radio yang selama ini bersiaran di Jakarta sekaligus mencari data terukur sebagai parameter untuk melakukan penilaian terhadap program isi siaran radio, termasuk pola mendengarkan radio pendengar radio seperti durasi dan tempat di provinsi DKI Jakarta. Metode penelitian berupa survei dengan sampel yang diambil sebanyak 1000 responden, margin of error 2.24% dan tingkat kepercayaan 95%. Metode pengambilan sampel dalam penelitian ini adalah dengan cara Multistage Random Sampling dari lima wilayah di provinsi DKI Jakarta. Teknik pengumpulan data adalah dengan wawancara perorangan secara tatap muka. Hasil penelitian mendeskripsikan profil pendengar radio di Jakarta adalah laki-laki atau perempuan yang bekerja dan berusia produktif dengan kemampuan ekonomi kelas menengah. Alasan utama mendengarkan radio adalah hiburan berupa musik. Mereka tergolong kategori Medium Listener dengan rata-rata lama jam mendengar per hari sebesar 1.87 jam namun dengan prime time sepanjang hari baik mendengarkan di rumah atau ketika sedang mengendarai mobil. Mereka sudah terpuaskan dengan acara dan program radio di Jakarta. Tingkat persaingan antara stasiun radio di Jakarta berdasarkan pendengar adalah Gen FM sebesar 44.6%, disusul oleh Bens Radio, Elshinta, I-Radio, Prambors dan CBB. Temuan menarik adalah fungsi radio untuk menyampaikan komunikasi sosial terpenuhi dengan menempatkan ceramah agama dan informasi sebagai program kedua dan ketiga yang paling disukai dengan 9.8% dan 8.0%, di bawah program musik.